2018
DOI: 10.1021/acs.jpcc.8b02053
|View full text |Cite
|
Sign up to set email alerts
|

Methoxy Formation Induced Defects on MoS2

Abstract: We find that exposure of the MoS2 basal plane to methanol leads to the formation of adsorbed methoxy and coincides with sulfur vacancy generation. The conversion of methanol to methoxy on MoS2 is temperature dependent. Density functional theory simulations and experiment indicate that the methoxy moieties are bound to molybdenum, not sulfur, while some adsorbed methanol is readily desorbed near or slightly above room temperature. Our calculations also suggest that the dissociation of methanol via O–H bond scis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…The deconvolution and peak fitting of the C 1s spectra during CH 3 OH dosing [Figure 1c] reveal the presence of the CH 3 O peak at 285.7 eV. 52,53 The CH 3 O formation is also confirmed from the weak peak at 530. ) may be present in small amounts as an intermediate product in dehydrogenation, its easy desorption to the gas phase (due to its small adsorption energy on the Cu surface) 18 makes it undetectable at low pressure.…”
Section: Methodsmentioning
confidence: 93%
“…The deconvolution and peak fitting of the C 1s spectra during CH 3 OH dosing [Figure 1c] reveal the presence of the CH 3 O peak at 285.7 eV. 52,53 The CH 3 O formation is also confirmed from the weak peak at 530. ) may be present in small amounts as an intermediate product in dehydrogenation, its easy desorption to the gas phase (due to its small adsorption energy on the Cu surface) 18 makes it undetectable at low pressure.…”
Section: Methodsmentioning
confidence: 93%
“…For instance, it has been shown that the exposure of MoS 2 to methanol (e.g., in a water/methanol system) can lead to the formation of sulfur vacancies. [120] The Li-intercalation-exfoliation is the other main type of exfoliation method for the production of TMDs, in which their parent crystals are immersed in a solution containing lithium ions such as hexyllithium or n-butyllithium under inert and dry conditions for a few days. During this process, Li intercalates into the interlayer spaces of TMDs and reacts to form compositions such as Li x MX 2 .…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%
“…[ 119 ] However, due to their significantly higher exfoliation energy (surface energy), [ 98 ] delamination of the TMDs is more difficult than graphene, which is a big challenge for the production of high concentration suspensions and ink formulation. Since the exfoliation method (e.g., the dispersion medium) can drastically affect the chemical/structural properties of the TMDs (will be discussed later), [ 120 ] and hence their performance, the exfoliation/synthesis of the 2D TMDs requires further attention. Therefore, before discussing the printing/coating of this group of 2D materials, their LPE, which is usually the starting point for ink formulation, will be briefly reviewed.…”
Section: Semiconductive Inksmentioning
confidence: 99%
See 1 more Smart Citation
“…11 It therefore calls for prudent ways to activate the basal plane of h-BN. Taking cues from prior studies on MoS 2 , [12][13][14][15][16][17] proposals have been made to activate the basal plane on h-BN by the creation of defects, 18,19 deposition of metal atoms or molecules, [20][21][22][23] creation of grain-boundaries, 24 and application of strain to the defective surface. 25 Quite akin to defect-laden single-layer MoS 2 (with sulfur vacancies), which calculations predict to be a possible catalyst for hydrogenation of syngas to alcohol, 12 the basal plane of the single-layer h-BN can be chemically activated for similar reaction, in the presence of point or line defects on the surface.…”
Section: Introductionmentioning
confidence: 99%